2015
DOI: 10.1016/j.bbi.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Daily positive events and inflammation: Findings from the National Study of Daily Experiences

Abstract: Background Inflammation is implicated in the development of chronic diseases and increases the risk of mortality. People who experience more daily stressors than others have higher levels of inflammation, but it is unknown whether daily positive events are linked to inflammation. Objective To examine the association of daily positive events with 3 inflammatory markers, interleukin-6 (IL-6), C-reactive protein (CRP), and fibrinogen. Method A cross-sectional sample of 969 adults aged 35–86 from the Midlife i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 56 publications
6
51
1
Order By: Relevance
“…The association between frequency of positive interactions and inflammation is consistent with the growing literature supporting an association of positive affect and daily positive events with circulating inflammatory markers (Stellar et al, 2015;Sin et al, 2015). For example, Sin and colleagues (2015) reported that positive interpersonal events were associated with lower IL-6 and fibrinogen in women.…”
Section: Discussionsupporting
confidence: 72%
“…The association between frequency of positive interactions and inflammation is consistent with the growing literature supporting an association of positive affect and daily positive events with circulating inflammatory markers (Stellar et al, 2015;Sin et al, 2015). For example, Sin and colleagues (2015) reported that positive interpersonal events were associated with lower IL-6 and fibrinogen in women.…”
Section: Discussionsupporting
confidence: 72%
“…During nightly telephone interviews, participants were asked whether any of these five positive events had occurred in the past 24 hours: (a) positive interpersonal interaction, (b) positive experience at work, school, or at a volunteer position, (c) positive experience at home, (d) network positive event (i.e., positive event experienced by a close friend or relative), and (e) any other positive event (Charles et al, 2010; Sin et al, 2015). For example, positive interpersonal interactions were assessed with the question, “Did you have an interaction with someone that most people would consider particularly positive (for example, sharing a good laugh with someone, or having a good conversation) since we spoke yesterday?” Participants were also asked to report what time the events happened.…”
Section: Methodsmentioning
confidence: 99%
“…Positive events were entered as a dichotomous variable (1 = positive event day, 0 = no positive event that day) when examined as a within-person predictor. 1 As a between-person predictor, the frequency of positive events was computed as the percent of study days during which at least one positive event occurred (Seltzer et al, 2009; Sin et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations